2018
DOI: 10.1016/j.qref.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Volatility spillovers between foreign exchange and stock markets in industrialized countries

Abstract: This paper empirically analyses the evidence of intra-spillovers and inter-spillovers between foreign exchange and stock markets in the seven economies which constitute the majority of foreign exchange transactions (i.e. the United Kingdom, the United States, the Euro area, Australia, Switzerland, Canada, and Japan). Daily data during the period 1 January 1990 to 31 December 2015 and during the pre-global and post-global financial crisis periods is used. To that end, we employ two econometric methodologies: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…To further confirm the existence of this effect, more accurate quantification is necessary in the following subsection. In line with our finding, Morales-Zumaquero and Sosvilla-Rivero [70] show that the US stock market is closely related to the other six stock markets, i.e., those of the UK, EU, Australia, Switzerland, Canada, and Japan.…”
Section: Results Of Comovements Identificationsupporting
confidence: 91%
“…To further confirm the existence of this effect, more accurate quantification is necessary in the following subsection. In line with our finding, Morales-Zumaquero and Sosvilla-Rivero [70] show that the US stock market is closely related to the other six stock markets, i.e., those of the UK, EU, Australia, Switzerland, Canada, and Japan.…”
Section: Results Of Comovements Identificationsupporting
confidence: 91%
“…Permanent component is dominated by the current expectation of permanent trend given (α + β) is less than one. Permanent or long-run component is mainly due to fundamental factors, whereas transitory or short-run component is mainly due to changes in financial markets as a result of the arrival of new information, speculation, and hedging positions (Chen & Shen, 2004;Morales-Zumaqueroa & Sosvilla-Rivero, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The significance of the coefficient of β 21 in model (10) describes long-run volatility or shortrun volatility spillovers from real stock price return to real exchange rate return. The SUR framework is used to estimate models 9 and 10 simultaneously (Bollerslev, 1990;Morales-Zumaqueroa & Sosvilla-Rivero, 2018). The SUR framework assumes that the errors are homoskedastic and linearly independent within each equation.…”
Section: Methodsmentioning
confidence: 99%
“…Sui and Sun [21] found stock return had a spillover effect between US and BRIC countries, and the short-term foreign exchange rate had significant spillover effects on stock return. Morales-Zumaquero and Sosvilla-Rivero [22] used the C-GARCH and SVAR methods to study the volatility spillover effects between the stock market and the foreign exchange market. ey found that the stock market played a leading role in volatility transmission, and the foreign exchange market was the main reason for the long-term volatility of the stock market.…”
Section: Literature Reviewmentioning
confidence: 99%